Exploration of importance of the ratification of the Council of Europe Convention on Prevention of Violence against Women by the Ukrainian Government - Koshulko, Oksana; Makazan, Evgenia (Technium Social Sciences Journal, 2020)
This paper presents the results of research on the importance of ratification by the Ukrainian government of the Convention on Prevention Violence against women. In this paper, primary and secondary data has been analysed. The primary data was collected through semi-structured interviews with Ukrainian women and the secondary data was collected from information on the websites of the United Nations in Ukraine, UN Women, the United Nations Population Fund, ILO and the Council of Europe. The research is significant because the Ukrainian State must use this Convention as a means of reducing domestic violence against women throughout Ukraine